Leadership handbook of management and administration - Berkley, James D., 1950- (Grand Rapids, Mich. : Baker Books, 2007)
This substantial resource offers pastors and church leaders practical insight into the daily issues of running a church. Conceived and compiled by the editors of Leadership journal, this book covers the full spectrum of ministry practice. Readers will learn about perennial topics such as time management, negotiating the terms of a call, handling crisis and conflict, hiring and managing staff, conducting special fund drives, spending church money, and dealing with tax and law considerations.
This revised and expanded edition of a proven ministry resource contains new contributions from prominent ministry leaders. Contributors include Leith Anderson, Rick Warren, Brian McLaren, Luis Palau, John Ortberg, Aubrey Malphurs, and many others.
pt. 1. The purpose of personal management / Darrell W. Johnson -- The call to ministry / Ben Patterson -- Our responsibility to God / James Earl Massey -- Responsibility to the ministry / Douglas D. Webster -- Responsibility to family members / Marshall Shelley -- Responsibility to self / Bill Hybels -- Time management / Peter F. Drucker -- Personal finances / Daniel D. Busby -- pt. 2. The meaning of church vocation / Bruce L. Shelley -- The search process / Douglas J. Rumford -- Negotiating the terms of a call / Edward B. Bratcher -- Making the move / Douglas G. Scott -- pt. 3. The meaning of leadership / Kenneth O. Gangel -- The responsibilities of leadership / Fred Smith, Sr. -- Leading Christians / Jack W. Hayford -- Crisis and conflict / William H. Willimon -- pt. 4. The meaning of supervision / Sharon G. Johnson -- Hiring support staff / Sylvia Nash -- Calling ministerial and program staff / Calvin C. Ratz -- Managing staff / Don Cousins -- Terminating staff / Paul Borthwick -- pt. 5. The meaning of volunteerism / Kenneth O. Gangel -- Volunteer recruitment / Leith Anderson -- Volunteer training / Kenneth O. Gangel -- Supporting volunteers / Mark H. Senter III -- pt. 6. The purpose of management / James E. Means -- Managing church government / Larry W. Osborne -- Managing the church office / David R. Pollock -- Managing the church computer system / Bryan E. Siverly -- Managing buildings and grounds / Robert H. Welch -- Managing construction and remodeling / R. Leslie Nichols -- pt. 7. The purpose of Stewardship / Richard B. Cunningham -- Planning stewardship / Victor D. Pentz -- Conducting special fund drives / Ann Rauvola Bailey -- Receiving and recording money / Mack Tennyson -- Managing and apportioning money / Gary Fenton -- Spending church money / Daniel D. Busby -- Tax and law considerations / Richard R. Hammar.
Includes bibliographical references and index.
Keywords: Church management; Christian leadership; Christian leadership; Church management